FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN DAN KESEJAHTERAAN PETANI GARAM RAKYAT KAWASAN PESISIR KALIANGET - Nurdody Zakki; Sayyida Sayyida (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2016)
The existence of the salt very important role in various fields of human life. To further facilitate the depiction of the benefits of salt in a wide range of human life. Weak capital owned by causing salt farmers are still not optimal in accessing the capital resources of banks and non-banks. Issues examined in this is how the influence of the type of business, venture capital and land ownership as well as its impact on the income of family welfare salt farmers, in order to know the influence of the type of business, venture capital and capital ownership to revenue and its impact on family welfare salt farmers. This research was conducted in the District Kalianget in the Pinggirpapas Village and Karanganyar village. In studies using quantitative descriptive research. The focus of this study examines the type of business, working capital, capital ownership, income and family welfare salt farmers. Samples were taken from two villages 100 salt farmers. The results of this study based on the analysis of logistics only land ownership is a factor which significantly affect the welfare and logit models produce Odds ratio here indicates the value of the tendency of a salt farmers who rent land to be living with the condition is very prosperous by almost 5 times more than salt farmer working other people's land. While the salt farmers who own land, tend to be more prosperous. This is indicated by the magnitude of the odds ratio which gives the meaning that the salt farmers who own land who live in a very prosperous condition of nearly 7 times more than farmers who enforces other people's land.Kata Kunci: Petani Garam, Kesejahteraan, Analisis Korelasi, Regresi Logistik.